2019
DOI: 10.3390/su11143887
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Management Practices within Agritourism Boarding Houses in Romania: A Qualitative Study Among Managers

Abstract: Small accommodation businesses such as agritourism boarding houses (ATBHs) provide a large share of accommodating capacity in certain rural destinations. Despite their small accommodation capacity, ATBHs consume substantial quantities of water and energy; this consumption implies high environmental costs. The present study aims to explore opinions of ATBH owner-managers regarding water and energy consumption in their businesses, what motivates them to adopt environmental practices, and the specific saving meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 108 publications
(147 reference statements)
1
13
0
Order By: Relevance
“…Some energy practices, specifically the use of LED lighting and Energy Star equipment, were widely adopted during the survey period and have a very short (good) financial return with a very small entry fee. This result is similar to previous research [74] that found the implementation of LED lighting was widespread in Dutch and Romanian tourism organizations. This may be explained by the low cost of implementation or the direct savings in energy billing [75], but also awareness of these practices is high [76] and their use is promoted by energy corporations across the United States [77].…”
Section: Addressing the Lack Of Practice Implementationsupporting
confidence: 92%
“…Some energy practices, specifically the use of LED lighting and Energy Star equipment, were widely adopted during the survey period and have a very short (good) financial return with a very small entry fee. This result is similar to previous research [74] that found the implementation of LED lighting was widespread in Dutch and Romanian tourism organizations. This may be explained by the low cost of implementation or the direct savings in energy billing [75], but also awareness of these practices is high [76] and their use is promoted by energy corporations across the United States [77].…”
Section: Addressing the Lack Of Practice Implementationsupporting
confidence: 92%
“…, 2021). Moreover, managers paid attention to environmental management practices to save energy and natural resources, reduce environmental problems generated by human activities and look after the natural environment in Romania (Ispas et al. , 2019).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Many accommodation sectors have increasingly implemented environmental management practices in order to demonstrate their environmental commitment to sustainable business management [4,15]. In general, environmental management practices (EMP) refer to implementing energy saving, waste management, recycling, eco-friendly products and eco-tours as part of the accommodation sector's business operation practices to achieve the goals of environmentally sustainable development strategies [1,16,17]. For example, making minor changes in the construction of the accommodation building, building man-agement and use of technology results in a cost-saving of 20-25% in the areas of energy usage, cleaning products or waste disposal [18].…”
Section: Literature Review 21 Environmental Management Practices In the Green Accommodation Sectormentioning
confidence: 99%